RANCANG BANGUN SISTEM INFORMASI MANAJEMEN SPARE PART MENGGUNAKAN QR CODE DI PT SAT NUSAPERSADA TBK - Tukino, Tukino (Universitas Putera Batam, 2023)
This study aims to describe the information system management of spare parts in PT Sat Nusapersada Tbk that has been applied and what problems have arisen and design a new system as a proposal of the problem of spare part management in PT Sat Nusapersada Tbk. To give an idea through the system design of the benefits of the system that makes it easy for users, the method used in this study is the waterfall. The results of this study indicate that the current system has the potential for errors in checking spare part stock data, reading the size of parts and also the slow management of stock data. With the new system design, it is expected to be able to control stock quickly, facilitate users in making reports, maximize business operations by using technology, and efficiently manage spare parts using qr code.